Implementasi Demokrasi pada Jenjang Perkuliahan - Audina, Selly Eka; Zahra, Naurah Salsabila Az; Baihaqi, Ahmad Rizal; Puspita, Ari Metalin Ika (TSAQOFAH, 2024)
Democracy as a system has been used as an alternative in various social and state activities in several countries, one of which is Indonesia which adheres to a democratic government system. Democracy as a state principle is essentially oriented towards the role of society in administering the state as the highest institution which aims to realize people's sovereignty. The application of democracy in Indonesia often experiences changes, there are several types of democracy such as: 1) democracy based on channeling the will of the people 2) democracy based on ideological principles 3) democracy based on the focus of attention. The democratic system implemented in Indonesia often experiences changes from democracy during the revolution (1945-1950), parliamentary democracy (1950-1959), guided democracy (1955-1966), democracy in the New Order government (1966-1998), democracy during the New Order era. reform (1999-present). In this research, the researcher wants to know about democracy at the college level. With that, researchers used qualitative methods. Qualitative methods are used to obtain in-depth data on research conducted. In this research, the data used is based on the results of interviews conducted directly with one of the sources, so that the data obtained can be verified as true. The research results show that democracy is a form of government in Indonesia, in which form of government the highest power is in the hands of the people. Apart from being applied in a democratic society, it is also applied at the college level. At the college level, democracy is applied to all students, namely by giving them the right to express their opinions and ideas. The implementation of democracy at the college level certainly cannot run smoothly without experiencing obstacles. However, apart from obstacles, there are also supporting factors that are driving the implementation of democracy at the college level.